Animal agriculture in Africa - socio-economic issues - Smalley, M.E. (South African Society of Animal Science, 1996)
The paper briefly describes the 2.6 times increase in the human population of sub-Saharan Africa expecte by 2025. Livestock already contribute about 35 percent of agricultural domestic product. The population increase, and attendant annual 7 percent rate of urbanisation will drive animal agriculture to intensify and become more commercially based. The paper goes on to describe socio-economic issues that must be taken into account as animal agriculture develops and intensifies. These are the multiple roles of livestock, livestock and land use, the impact on households of the control livestock diseases, and women farmers-work, cash and extension advise. Local communities have traditionally led the Development of their agricultural systems to meet human and environmental needs. Now many traditional mechanisms are breaking down. New technologies that address these breakdowns and meet the requirements of intensified production must not ignore underlying socio-economic issues. Women are central to agriculture, and to animal agriculture. They already provide 46 percent of labour and produce 70 percent of Africa's food. However, many new technologies increase the work load of women. Furthermore, women often fail to directly receive extension advice, do not control resources or decision making, nor control the extra income generated. Research and extension systems must take account of these problems. Finally the paper argues that all levels of the educational process in sub-Saharan Africa must get agriculture and practical aspects of agriculture into the curricula. This is essential to ensure effective research, to achieve the best delivery of extension advice, and to create a new generation of farmers able to participate in the intensification and commercialisation of agriculture over the next 25 years.